Development of the digestive tract in first feeding larvae of Betta splendens Regan, 1910 - Silva, R. C. [UNESP]; Valentin, F. N. [UNESP]; Paes, M. C. F. [UNESP]; Faustino, F. [UNESP]; Giannecchini, L. G. [UNESP]; Viadanna, P. H. O. [UNESP]; Nascimento, N. F. [UNESP]; Fernandes, J. B. K. [UNESP]; Nakaghi, L. S. O. [UNESP] (Wiley-Blackwell, 2016)
The aim of this study was to analyse the development of the digestive tract of Siamese fighting fish larvae (Betta splendens Regan, 1910), from hatching to 92hours post-hatching (hph) at 28.0 degrees C, in order to determine the most appropriate time to begin exogenous feeding (live feed) and to investigate the digestive tract and its function during larval development. At hatching (29hours post-fertilization), the digestive tract was a simple and straight undifferentiated tube lined by a single layer of columnar epithelial cells; the mouth and anus were closed. At 18hph, the mouth was open. At 32hph, the tongue was located in the depression of the buccopharyngeal cavity floor and supported by basal cartilage. Goblet cells were present in the epithelium lining the pharynx and oesophagus. At 56hph, the midgut had four distinct layers: the mucosa with typical villi, the submucosa, the smooth muscle layer, and the serosa. Histological analysis revealed that the larvae retained endogenous yolk reserves until 74hph. Lipid accumulation was observed in the liver, which coincided with complete yolk absorption. At this time, the digestive tract was fully open and functional. Thus, it can be concluded that live feed should be given to B.splendens larvae from 74hph onward, when the larvae are able to consume the food provided. This study also provides useful data for the improvement of husbandry techniques and for the formulation of diets specific to ornamental fish larvae.